PENGARUH MINAT BELAJAR DAN KECERDASAN INTELEKTUAL MAHASISWA TERHADAP PRESTASI BELAJAR PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Mawardi Nurullah (Prodi PPKn FKIP Universitas Pamulang, 2018)
The purpose of this study is to determine the interests and intellectual intelligence together with the achievement of Pancasila and Citizenship Education learning on semester 1 students of Pamulang University. That interest in learning is something that can awaken or encourage a person to be diligent in learning to achieve the desired goals by trying to know, follow, understand, concentrate, to achieve high achievement. In the learning activities of each learner will be influenced by his intellectual intelligence personally. Through the intellectual intelligence of the students are trying to set goals that must be achieved. The results of this study found that Achievement learning Citizenship Education on average is 66,825 and there are still 40% who have values below the average so categorized quite good or moderate. Improvement of learning achievement of Pancasila and Citizenship Education (PPKn) can improve student's interest in learning better. Second, the results showed the dominant influence of intellectual intelligence is higher than the interest in learning. Therefore, the intellectual intelligence of students is always honed, so often given the task of homework both individually and in groups. Third, further research is needed which includes variables other than the interest in learning and intellectual intelligence as a complete predictor of Pancasila and Citizenship Education achievement. Moreover, there are still 50.1% sources of variation that cannot be explained by interest in learning and intellectual acumen.